Factors affecting antibiofilm properties of microbial surfactants - Pirog, Tatiana; Kliuchka (Nykytyuk), Lilia; Lutsay, Dariya; Stabnikov, Victor (My University, 2021)
Antibiofilm activity of surface-active substances (SAS) synthesized by Rhodococcus erythropolis, Acinetobacter calcoaceticus, or Nocardia vaccinia was studied. The strains were cultivated using carbon ethanol, glycerol, hexadecane, sunflower oil, and carbon-containing wastes from biodiesel production as carbon sources. Escherichia coli, Bacillus subtilis, Staphylococcus aureus, Pseudomonas aeruginosa, and yeasts Candida albicans and Candida utilis were used as testing cultures. The antibiofilm activity of biosurfactants depended on the source and concentration of carbon source and duration of cultivation. The addition of calcium cations to media significantly increased antibiofilm activity. Replacement of pure sources of carbon for wastes provided the opportunity to receive biosurfactants with high antibiofilm properties on inexpensive substrates. Destruction of biofilms was the same in cases when supernatant or purified SAS was used. Вивчено антибіоплівкову активність поверхнево-активних речовин (ПАР), синтезованих Rhodococcus erythropolis, Acinetobacter calcoaceticus або Nocardia vaccinia. Штами культивували з використанням в якості джерел вуглецю вуглецевого етанолу, гліцерину, гексадекану, соняшникової олії та вуглецевмісних відходів виробництва біодизеля. Як тест-культури використовували Escherichia coli, Bacillus subtilis, Staphylococcus aureus, Pseudomonas aeruginosa, дріжджі Candida albicans і Candida utilis. Антибіоплівкова активність біосурфактантів залежала від джерела та концентрації джерела вуглецю та тривалості культивування. Додавання до середовищ катіонів кальцію значно підвищувало активність антибіоплівки. Заміна чистих джерел вуглецю на відходи дала можливість отримувати на недорогих субстратах біоПАР з високими антибіоплівковими властивостями. Деструкція біоплівок була однаковою у випадках використання супернатанту або очищеного ПАР.
Keywords: біоплівки; поверхнево-активні речовини; культивування; кафедра біотехнології і мікробіології; biofilms; biosurfactants; cultivation